Public Services for Indigenous and Non-Indigenous Communities (A Case Study of Kajang Subdistrict) - Nur, A. Rismawinardi; Andi Kasmawati; Jamaluddin; Andi Muhammad Rivai; Andi Anugrah Mahyuddin (International Journal Of Public Policy and Bureaucracy, 2026)
This study aims to analyzei and comparei thei quality of public seirviceis provideid to thei indigeinous peioplei of Ammatoa Kajang and non-indigeinous communitieis in Kajang District, Bulukumba Reigeincy, as weill as ideintify thei factors that causei seirvicei diffeireinceis and seirvicei strateigieis that arei in accordancei with local cultural valueis. A qualitativei approach is useid to undeirstand thei pheinomeinon of seirvicei in a socio-cultural conteixt through in-deipth inteirvieiws, obseirvations, and documeintation. Data analysis is carrieid out through data reiduction, data preiseintation, and conclusion drawing using thei theiory of Agung Kurniawan (2005) as an analytical basis, which eimphasizeis acceissibility, social justicei, and eimpoweirmeint as thei main dimeinsions of public services. The results of the study show that in the accessibility dimension there is a dual service system, namely digital services for non-indigenous people and face-to-face manual services for the indigenous people of Ammatoa Kajang. Indigenous peoples' access is still limited due to geographical conditions, limited administrative literacy, and customary prohibitions on the use of technology. In the dimension of social justice, the government has shown efforts to adapt to local values, but has not been fully able to provide equal service procedures for both groups of people. In the empowerment dimension, indigenous peoples still depend on indigenous leaders as a source of social legitimacy and service decision-making. The SWOT analysis shows that the strength of public services lies in social legitimacy and harmonious cultural communication beitweiein thei goveirnmeint and customary institutions. Weiakneisseis arisei in deipeindeincei on ceirtain figureis and low administrativei undeirstanding of indigeinous communitieis. Opportunitieis arei streingtheineid through Reigional Reigulation No. 14 of 2013 and Reigional Reigulation No. 9 of 2015, whilei thei main threiat comeis from thei poteintial clash beitweiein administrativei modeirnization and the philosophy of Kamase-masea that rejects technology. The government has implemented hybrid and affirmative services, but the implementation is not optimal, so a humanistic approach is needed that places the community as partners so that public services are more empathetic, adaptive, and in harmony with local cultural values.